APTAMERS: A NOVEL APPROACH FOR BIO-IMAGING, BIO-SENSING AND TARGETED DRUG DELIVERY SYSTEMS - Upadhyay, Nisha; Vyas, Maulesh; Behera, Atanu; Shah, Megha; Meshram, Dhananjay (Innovare Journal of Life Sciences, 2013)
This review describes recent progress made in the aptamer and application of biomedically relevant aptamers and relates them to their future clinical prospects. Aptamers are single-stranded nucleic acid or amino acid polymers that recognize and bind to targets with high affinity and selectivity. In nature they exist as a nucleic acid based genetic regulatory element called a riboswitch. Aptamers, simply described as chemical antibodies, are synthetic oligonucleotide ligands or peptides that can be isolated in vitro against diverse targets including toxins, bacterial and viral proteins, virus-infected cells, cancer cells and whole pathogenic microorganisms. They are isolated by the technique called SELEX- systematic evolution of ligands by exponential enrichment. The applications of aptamers range from diagnostics and biosensing, target validation, targeted drug delivery, therapeutics, templates for rational drug design to biochemical screening of small molecule leads compounds, in virology,as novel radio pharmaceuticals. Â 